ADOPTING NEW MANAGEMENT TECHNOLOGIES FOR BETTER TOURIST EXPERIENCES IN MALAYSIA’S TOURISM SECTOR - Osman, Zamri Bin (Sharia Business Management UIN Raden Intan Lampung, 2023)
The effect of Augmented Reality (AR) and Virtual Reality (VR) on the Malaysian tourism business is looked into in this study. With tourism at the forefront of this digital transformation, AR and VR have emerged as revolutionary forces, revolutionising a wide range of businesses. While Virtual Reality immerses viewers in a virtual environment, Augmented Reality enhances real-life experiences by superimposing digital information on top of the physical world. The entire visitor experience—from planning and booking to on-site exploration and post-trip comments—has been changed by AR and VR. While virtual reality (VR) technologies offer deep participation in several exciting activities and provide a fascinating insight into the destination's attractions, augmented reality (AR) applications enhance the tourist experience by giving interactive maps, historical insights, and real-time translations.